HOW TO POVERTY AND CONTRIBUTIONS FOR TOURISM IN WEST SUMATRA - mike triani (Jurnal Ilmiah Ekonomi Dan Bisnis, 2019)
How the Influence the tourism sector contributes to poverty in the province of West Sumatra. The data used is secondary data from the combination of time series and cross section from 2015 to 2017, with documentation from collection institutions and agencies. The research methods used are: (1) Fixed Effect Analysis (FEM), (2) Classical Assumption Test . The regional income from the tourism sector contributes to the reduction of poverty in the province of West Sumatra but is not significant. (2) The number of hotels in the province of West Sumatra. (3) Micro small and medium enterprises contributing to the poverty reduction in the province of West Sumatra but is not significant. (4) The regional revenue of the tourism sector, the number of hotel rooms, and the micro and small enterprises together has a significant contribution to poverty in the province of West Sumatra.